2020
DOI: 10.1186/s12905-020-01115-1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and violence: a research call to action

Abstract: COVID-19 related guidelines and movement restrictions are designed to protect the public’s health and reduce disease transmission; yet, COVID-19 related restrictions on movement including social distancing, isolation, quarantine, and shelter-in-place orders have an unknown effect on violence and abuse within relationships. As the pandemic has progressed, many have justifiably speculated that such restrictions may pose a danger to the safety and well-being of people experiencing such violence. Early in the pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 6 publications
0
34
0
3
Order By: Relevance
“…via tweets. Also for this problem, a solidarity support from community by additional resources provided by governments in the first surge of this pandemic in regard of health professionals is particularly valuable 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…via tweets. Also for this problem, a solidarity support from community by additional resources provided by governments in the first surge of this pandemic in regard of health professionals is particularly valuable 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…, 2020 ; Moise, 2020a ) including those on households across the United States of America (USA), and Miami-Dade County, Florida, the study site for our work, is no exception, and one that evinced significant cases, hospitalizations, and deaths (Piquero and Kurland, 2021 ). Of particular concern is the effect of the dual stress incited by “facing a pandemic” and “shelter-in-place orders” on mental health (Du et al, 2020 ), raising concerns about the safety and well-being of people experiencing violence and abuse within relationships (Evans, 2020 ). However, the evidence of “shelter-in-place orders” on crime has been mixed, with some studies reporting decreases in crime (Ashby, 2020 ; Boman and Gallupe, 2020 ), while others report increases in specific types of crime such as homicide (Rosenfeld and Lopez, 2020 ) and domestic violence (Piquero et al, 2021 ), with mixed findings regarding associated predictors (Campedelli et al, 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigated risk factors for crime include substance use, economic stress, financial stress, and food insecurity (Gibbs et al, 2018 ), and many of these factors are likely to worsen in the context of a pandemic (Evans, 2020 ), with increases in exposure to various types of strainful events (Agnew, 1992 ) and changes in routine activities (Cohen and Felson, 1979 ). Furthermore, crime in one area can disproportionately impact on residents of adjacent communities’ well-being (Kling, Liebman, and Katz, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…The factors that influence the high rate of violence against women can then be overcome by knowing the preventive interventions that can be pursued. The New Normal era, which currently continues to coexist with the COVID 19 pandemic case with fluctuative numbers, is an urgent matter that needs attention (Evans, 2020;Oguntayo et al, 2020). In addition, the existing policy on sanctions against perpetrators of violence against women also needs to be assessed for its application.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that lockdown and work from home policies affect the dynamics in families, especially families with middle and low socioeconomics such as decreased family income, increased stress and are more prone to anger. (Evans, 2020;Fontanesi Daniela;Mazza, Cristina;Di Giandomenico, Serena;Roma, Paolo;Verrocchio, Maria Cristina, 2020;Oguntayo et al, 2020). Fear, anxiety and psychological distress due to prolonged territorial restrictions, closure of schools for children, economic strain and conditions of vulnerability to viruses or uncertainty about life have dramatic effects.…”
Section: Introductionmentioning
confidence: 99%